The Relationship between Fatigue Levels and Work-Related Musculoskeletal Disorders (WMSDs) Complaints on Yogyakarta Online Taxi Bike - Faidlullah, Hilmi Zadah; Ariyanto, Andry; Surani, Alena Vidia (Ikatan Fisioterapi Indonesia, 2022)
Background: Transportation is something that people really need. An online motorcycle taxi application is one mode of transportation that can be used to make it easier for consumers to carry out various activities. Online motorcycle taxi drivers are one of the workers who are at risk of experiencing fatigue due to increased orders in online motorcycle taxi applications. Method: This study employed quantitative research design with a cross sectional design. The research sample was taken by purposive sampling technique with a sample size of 100 people. The research instrument used was a Nordic Body Map (NBM) questionnaire to measure musculoskeletal complaints and the Industrial Fatigue Research Committee (IFRC) to measure fatigue during work. Data analysis was done using Spearman correlation test. Result: As many as 80% of taxi bike drivers suffer from musculoskeletal disorders, particularly in the neck, back, and hands. As many as 74% of them reported feeling tired. The Spearman Rank correlation test results show a link between fatigue and complaints of Work-Related Musculoskeletal Disorders (WMSDs) on online taxi bike in Yogyakarta (r = 0.264, p = 0.008). Conclusion: There is a relationship between the level of fatigue and complaints of Work-Related Musculoskeletal Disorders (WMSDs) on online motorcycle taxis in Yogyakarta. Further researchers should include other variables related to complaints about online motorcycle taxis.